2014
DOI: 10.3389/fnhum.2014.00120
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions in developmental dyslexia

Abstract: The present study was aimed at investigating different aspects of Executive Functions (EF) in children with Developmental Dyslexia (DD). A neuropsychological battery tapping verbal fluency, spoonerism, attention, verbal shifting, short-term and working memory was used to assess 60 children with DD and 65 with typical reading (TR) abilities. Compared to their controls, children with DD showed deficits in several EF domains such as verbal categorical and phonological fluency, visual-spatial and auditory attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 101 publications
(138 reference statements)
7
104
0
11
Order By: Relevance
“…Whilst central executive problems may be most strongly expressed on tasks tapping the function of the phonological loop, there is a growing corpus of research indicating that central executive problems can also be found on visuospatial working memory tasks (e.g., Bacon et al, 2013;Menghini, Finzi, Carlesimo & Vicari, 2011;Olson & Datta, 2002;Swanson, 1992;Swanson, 1999;Varvara, Varuzza, Sorrentino, Vicari & Menghini, 2014), particularly when conditions are cognitively taxing or novel (e.g., Smith-Spark et al, 2003, Smith-Spark & Fisk, 2007. Therefore, it was predicted that executive-loaded working memory deficits would be found across both the phonological and visuospatial domains.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst central executive problems may be most strongly expressed on tasks tapping the function of the phonological loop, there is a growing corpus of research indicating that central executive problems can also be found on visuospatial working memory tasks (e.g., Bacon et al, 2013;Menghini, Finzi, Carlesimo & Vicari, 2011;Olson & Datta, 2002;Swanson, 1992;Swanson, 1999;Varvara, Varuzza, Sorrentino, Vicari & Menghini, 2014), particularly when conditions are cognitively taxing or novel (e.g., Smith-Spark et al, 2003, Smith-Spark & Fisk, 2007. Therefore, it was predicted that executive-loaded working memory deficits would be found across both the phonological and visuospatial domains.…”
Section: Discussionmentioning
confidence: 99%
“…They do not always show consistent results-some of them confirm significant EF deficits in these individuals, others indicate a similar level of performance in the EF tasks by children and adults with dyslexia as compared to controls (Booth et al, 2010). EFs such as auditory attention, visual-spatial attention, short-term verbal and visual memory, visual working memory as well as verbal shifting were analysed in the studies mentioned (Varvara et al, 2014). It means that cognitive deficits in reading disorders may be limited to more specific mechanisms within individual executive function (Swanson, 2006).…”
Section: Reading Abilities Executive Functions and Working Memorymentioning
confidence: 94%
“…There is a relatively small body of research which would address executive functions in the context of literacy, both in developmental and clinical studies (Booth, Boyle & Kelly, 2010;Jabłoński, 2013;Varvara, Varuzza, Sorrentino, Vicari & Menghini, 2014;Walda, van Weerdenburg, Wijnants & Bosman, 2014).…”
Section: Reading Abilities Executive Functions and Working Memorymentioning
confidence: 99%
“…Os estudos mostram que não há déficit no componente visuoespacial da MT em disléxicos (CRUZ-RODRIGUES et al, 2014;VARVARA et al, 2014), apenas quando associado ao CI (BOOTH et al, 2014). Segundo Brosnan et al (2002), o CI e a MT não podem ser descritos de forma isolada, pois ambos são interdependentes e pertinentes para entender a dislexia.…”
Section: Memória De Trabalhounclassified
“…Isso se dá pelo fato da dislexia apresentar déficit multifatorial, e sua disfunção não ser limitada apenas às áreas linguísticas do cérebro, sendo que diferentes indivíduos podem apresentar deficiências neuropsicológicas e dificuldades cognitivas distintas nas avaliações, porém no conjunto, manifestarem habilidade de leitura igualmente pobre (MENGHINI et al, 2010;VARVARA et al, 2014). Isso é possível verificar no estudo de Menghini et al (2010) que avaliou 60 disléxicos e identificou que apenas 18,3% deles apresentou déficit fonológico exclusivamente, e que 76,6% mostraram outros déficits além do fonológico, sendo 38,2% deles com déficit nas FE.…”
Section: Funções Executivas Como Preditoras Da Dislexiaunclassified